2021
DOI: 10.1002/ijop.12771
|View full text |Cite
|
Sign up to set email alerts
|

Chinese perceive upward social mobility: How future mobility is influenced, but not limited by past mobility

Abstract: P erceptions of social mobility vary across countries. However, past studies have mostly focused on populations in Western developed countries. Little is known about perceptions of social mobility in non-Western developing countries. The current paper focuses on Chinese perceptions of social mobility using a large-scale nationally representative sample. We found that, overall, Chinese believed in upward social mobility. Moreover, different patterns of perceptions of social mobility were identified, which sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Our findings are in line with the previous research, including from China, suggesting that previous social mobility is one of the key explanations for individuals' perceptions (Du et al, 2021;Gugushvili 2021a;Lipset 1992). Poland is characterized by relatively high levels of income inequality, which is known to affect the patterns of social comparison Wilkinson & Pickett, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with the previous research, including from China, suggesting that previous social mobility is one of the key explanations for individuals' perceptions (Du et al, 2021;Gugushvili 2021a;Lipset 1992). Poland is characterized by relatively high levels of income inequality, which is known to affect the patterns of social comparison Wilkinson & Pickett, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Our results may also suggest that individuals desire to use elitism as a means to move up the social ladder, particularly when social mobility within their society is relatively low. A recent survey on social mobility within China demonstrated that despite having experienced downward social mobility, Mainland Chinese participants still believe that upward social mobility is possible (Du et al, 2021). These findings affirm that Mainland Chinese aspire to improve their social standings despite prior setbacks.…”
Section: Discussionmentioning
confidence: 99%
“…According to Du and his colleagues (2021), socio-economic mobility is shaped by past experiences of mobility. With a better understanding of the youth’s perception of socio-economic mobility, a more concrete and fair explanation of future mobility can be projected (Du et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%